Occurrence of Potato Cyst Nematode, Globodera rostochiensis, on Potato in the Saint-Amable Region, Quebec, Canada - Sun, F; Miller, S; Wood, S; Côté, M-J (Plant disease, 2007)
Potato (Solanum tuberosum L. subsp. tuberosum) is one of the most important food crops in Canada. Potato cyst nematodes, Globodera rostochiensis (Wollenweber, 1923) Skarbilovich, 1959 and Globodera pallida (Stone, 1973) Behrens, 1975, are considered the most economically important nematode pests of potatoes worldwide and are the subject of strict quarantine regulations in many countries including Canada. In Canada, G. rostochiensis was found in the Saanich Peninsula of Vancouver Island, British Columbia and both G. rostochiensis and G. pallida are present on the island of Newfoundland (3). During August of 2006, soil and roots of potato plants collected from a 19.2-ha field in the Saint-Amable region, Quebec, were submitted to the Nematology Laboratory, Canadian Food Inspection Agency, Ottawa. Golden, spherical-shaped cysts were found associated with the roots and were also extracted from the soil. The nematodes recovered were identified by morphological and morphometric analysis and DNA analysis. Measurements and morphological observation of 60 second-stage juveniles were as follows: body length = 427.4 ± 22.0 (395 to 495) μm; stylet length = 21.3 ± 1.2 (18 to 23) μm; distance from stylet base to dorsal esophageal gland opening = 5.5 ± 0.9 (3.5 to 7.0) μm; tail length = 46.7 ± 3.7 (36 to 58) μm; hyaline tail terminus = 21.1 ± 3.1 (13 to 27) μm; and the shape of stylet basal knobs varied from rounded to lateral flattened. Observations for 35 mature cysts were: number of cuticular ridges between anus and vulval fenestra = 21 ± 6 (12 to 31); fenestral length = 18.4 ± 3.6 (11 to 30) μm; distance from anus to the edge of fenestra = 81.1 ± 30.4 (29 to 165) μm; Granek's ratio = 4.4 ± 1.6 (1.8 to 6.0), with parallel wavy cuticular ridges between anus and vulval fenestra. These observations conformed to the published description of G. rostochiensis (2). Additionally, the identification was supported by the PCR-restriction fragment length polymorphism pattern of the ITS-1 region amplified using primers 18S (5'-TTGATTACGTCCCTGCCCTTT-3') and rDNA1.58S (5'-ACGAGCCGAGTGATCCACCG-3') and digested with BstU I and a PCR product specific for G. rostochiensis (1). Sequence of a 1,190-bp PCR fragment of ribosomal DNA amplified using primers rDNA1 (5'-TTGATTACGTCCCTGCCCTTT-3') and rDNA2 (5'- TTTCACTCGCCGTTACTAAGG-3') showed 99.0 to 100% identity with published DNA sequences of the same genomic region for G. rostochiensis (4). The sequence is available from the authors upon request. The origin of the introduction of G. rostochiensis into Saint-Amable is unknown. An intensive soil survey is underway to define the infested area, and strict quarantine measures have been taken to prevent further spread of G. rostochiensis. To our knowledge, this is the first evidence of the occurrence of G. rostochiensis in Quebec, Canada. References: (1) A. Fullaondo et al. Nematology 1:157, 1999. (2) A. M. Golden et al. Proc. Helminthol. Soc. Wash. 39:64, 1972. (3) A. R. Stone et al. Plant Dis. Rep. 61:590, 1977. (4) S. A. Subbotin et al. Nematology 2:591, 2000.